Investigating EFL Learners’ Recognition of Conversational Implicature in Listening Test - Safitri, Luh Mega; Suastra, I Made; Beratha, Ni Luh Sutjiati; Netra, I Made (RIRAI Publisher, 2024)
In arrange to progress the capacity of tuning in comprehension, it's essential for English learners to be presented with a few essential Pragmatics speculations. Grice's Conversational Implicature Hypothesis is one of the foremost imperative substance of Pragmatics . This study aims to analyse the short conversations in the listening comprehension of TOEFL test from the perspective of pragmatics. Hence, this study was done to identify EFL learners’ capability in comprehending and producing implicature. Data were analysed using the theory of Conversational Maxims proposed by Grice (1975). The researcher applied a descriptive qualitative research method using survey and interviews method for data collection in EFL classroom. The participants of this research were three classes in Bali International Polytechnic consisting of 30 students. The data was collected through assigning a listening comprehension test and further interviews on Bali International Polytechnic students. The study found only few students who get the score above 80, lacking tuning in comprehension ought to mostly account for the blunders made in these questions, but through the examination, the most reason is the students' trouble in inducing the speaker's verifiable meaning. Most of the students found the difficulties in comprehending the implied meaning or conventional implicatures. There are five difficult aspects of understanding listening test namely conversational implicature knowledge, idiomatic expression, lack of vocabulary, need of concentration, and new accent. Encourage, the part of conversational impersonation in tuning in comprehension of the TOEFL test is exceptionally critical. Grice's conversational implicature can be adjusted to the instructing of tuning in by giving both speakers and understudies with a way of how specific articulation implications are passed on and decoded in particular settings of circumstance. In this way, the discoveries demonstrate that the English learners ought to ace the hypothesis of Grice's Conversational Implicature, learn how to induce implicature to direct their learning and lead in such hypotheses in tuning in comprehension.